Ekstrak Propolis sebagai Imunomodulator - Irma L. M.; Syamsudin Syamsudin; I. W.T. Wibawan (Fakultas Farmasi Universitas Pancasila, 2006)
A study was done to evaluate the effect of propolis on phagocytic activity and capacity of cells phagocyts with induction SGB (Streptococcus Grup B). In vivo methods were used on the study. In vivo study treatments were divided in four groups. Each group was inducted by 109 cell/ml of SGB. The group consists of treatment by given propolis at dosage 25 mg/kgBW, 50 mg/kgBW, 100 mg/kgBW, and group control, not given propolis. The result showed activity dosage value of propolis were significantly different (p<0.01) at dosage 50 mg/kgBW and capacity dosage value of propolis were significantly different (p<0.01) at dosage 100 mg/kgBW.